(untitled) (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2026)
The study of magnetoelastic effects is constantly topical, on the one hand because it allows for the deepening of the knowledge of magnetization processes in ferromagnetics, and on the other hand because new scientific and technical applications of these effects are always emerging. In Romania, magnetoelasticity problems have been the subject of intense research in Timisoara and Craiova, where magnetoelastic effects related to torsional stress played an important role[1,2]. The main magnetostrictive/magnetoelastic effects were discovered in the 19th century: Joule (1842), Matteucci (1847), Vilari (1865), and Wiedemann (1895), on the basis of which hundreds of patents were realized. [3,4] The new magnetoelastic torque transducers represent advances in non-contact torque measurement technology, often offering improved sensitivity, accuracy and integration for modern applications such as: electric vehicles (EV, PHEV) requiring accurate torque monitoring for battery management, transmission optimization and regenerative braking systems, motorsport (Formula 1, Formula E), wind power installations, avionics, robotics, etc. Magneto-elastic tensiometry allows the original shaft of the power unit to be used as the sensitive element (without the series introduction of a special measuring device). The principles of torque measurement based on the modification of the magnetic properties of the shaft itself or of an active (amorphous) magnetic layer deposited on the surface of the original shaft are described.